Analisis Kinerja Aparatur Sipil Negara Bidang Pendidikan Madrasah di Kantor Wilayah Kementerian Agama Provinsi Sumatera Utara - Surya Ningsih Damanik (VISA: Journal of Vision and Ideas, 2022)
The purpose of this study is to assess the performance of the State Civil Apparatus in the field of madrasa education at the ministry of religion's regional office in North Sumatra. Interviews, observations, and documentation were used to collect descriptive qualitative research data from information sources and important information sources. The reduced study data is presented, and conclusions are reached. (1) Employees attempted to complete tasks on time, but obstacles arose, causing work to be delayed; however, at the regional office of the Ministry of Religion of the North Sumatra Province, employees were not required to complete tasks on time, but the contents of the report could be collected at the end of the month. This situation arises as a result of restricted facilities and officer numbers, as well as the load of jobs that must be completed simultaneously, as well as assignments out of town or attendance at meetings, causing work to be delayed. (2) Employees attempt to change working hours that have been set because they are mandatory, and if they are not disciplined, they will be subjected to administrative sanctions in the form of allowances and sanctions under Government Regulation Number 53 of 2010 about Civil Servant Discipline. (3) Employees make an effort to demonstrate their abilities at work. (4) In order to complete work more quickly, leaders and subordinates collaborate. Keywords: Evaluation, Performance, State Civil Apparatus